ACTUAL PROBLEMS OF INCREASING THE COMPETITIVENESS OF MACHINE-BUILDING ENTERPRISES IN MODERN CONDITIONS - N. Arsenieva; L. Putyatina; A. Zheltenkov (Вестник университета, 2019)
The article has devoted to the issues of improving the competitiveness of enterprises in the engineering industry. The factors hindering the development of industry enterprises have been analyzed. The article substantiates the main components of the competitiveness of enterprises, which are of particular relevance: product range – technology; – advanced R & d; – economic, industrial and innovative potential, etc. the Possibilities of improving the competitiveness of enterprises at the level of macroeconomics and at the level of enterprises themselves have been considered. The method of calculation, allowing to draw conclusions about the competitiveness of the product range of the enterprise has been offered.